Cross-national knowledge transfer, absorptive capacity, and total factor productivity: the intermediary effect test of international technology spillover. Issue 6 (3rd June 2022) - Yu, Haichao; Zhang, Jianqing; Zhang, Minqi; Fan, Fei
ABSTRACT: Knowledge has become the most important factor of production with the emergence of the knowledge economy. We use the system GMM estimation method to analyze how cross-national knowledge transfer (CNKT) impacts the total factor productivity (TFP) of China's 31 provinces and evolution of China's ability to absorb foreign knowledge. We also examine the possible intermediary effects of foreign direct investment (FDI), outward FDI, import trade, export trade, and direct technology spillovers between CNKT and TFP. We find that: (1) CNKT improves China's TFP and positively impacts FDI, import trade, export trade, and direct technology spillover; It shows that CNKT not only helps to improve China's TFP, but also provides innovative knowledge reserve for the absorption of international technology spillovers. (2) The improvement in the domestic infrastructure construction level, R&D capacity, human capital, economic development and openness has obvious absorption effect on CNKT, which is conducive to the absorption and utilisation of international advanced knowledge. (3) FDI, import trade, and direct technology spillover play a partial mediating role between CNKT and TFP, and the intermediary effect of import trade technology spillover is the strongest.